Portable mobile surveillance - Ang, Guo Tai (2012)
Security at home is one of the main concerns in mind when people leave their home unattended, be it going to work or going on an oversea trip. Home surveillance can be used to monitor activities related to security or intrusion of privacy. It can also be used as a monitoring tool to check on the situation at home.